2011
DOI: 10.1590/s0074-02762011000300004
|View full text |Cite
|
Sign up to set email alerts
|

Bat flies on phyllostomid hosts in the Cerrado region: component community, prevalence and intensity of parasitism

Abstract: Streblidae flies are specialised parasites of bat hosts, mainly phyllostomids. There is a high richness of streblids in the savannah-like Cerrado region; however, there is little quantitative data available in parasitological indices. Here, we describe the component community, prevalence and intensity of a streblid infestation on a phyllostomid bat assemblage in Serra da Bodoquena, a Cerrado region in Southwest Brazil. We conducted surveys by capturing and inspecting bat hosts during the seven-month period bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
34
2
23

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 25 publications
(69 reference statements)
9
34
2
23
Order By: Relevance
“…In addition to the new records of associations (Table I), we found the following variations in the component communities: the absence of Paraeuctenodes similis Wenzel, 1976 on C. perspicillata, association observed in regions of Atlantic forest (Bertola et al in 2005, Prevedello et al 2005 and Amazon forest (Guerrero 1996); the absence of Metelasmus pseudopterus Coquillet, 1907, which is found parasitizing species of Artibeus from the south-central Brazil (Eriksson et al 2011, Bertola et al 2005; the lower number of ectoparasitic species on Desmodus rotundus (E. Geoffroy, 1810), that in other areas of cerrado is also parasitised by Trichobius furmani Wenzel, 1966 and Strebla wiedemanni Kolenati, 1856 (Eriksson et al in 2011, Aguiar andAntonini 2011); the absence of Trichobius uniformis Curran, 1935 andStrebla curvata Wenzel, 1976 on Glossophaga soricina (Pallas, 1766), found on this species in cerrado areas (Eriksson et al 2011, in addition to the parasitism by Paraeuctenodes longipes Pessoa et Guimaraes, 1937 recorded in the southern Brazil (Graciolli and Rui 2001). It is also highlighted the absence of parasitism on A. cinereus, a species with register of parasitism by ectoparasitic flies of the genus Neotrichobius Wenzel and Aitken, 1966 in the Amazon region (Guerrero 1994a).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…In addition to the new records of associations (Table I), we found the following variations in the component communities: the absence of Paraeuctenodes similis Wenzel, 1976 on C. perspicillata, association observed in regions of Atlantic forest (Bertola et al in 2005, Prevedello et al 2005 and Amazon forest (Guerrero 1996); the absence of Metelasmus pseudopterus Coquillet, 1907, which is found parasitizing species of Artibeus from the south-central Brazil (Eriksson et al 2011, Bertola et al 2005; the lower number of ectoparasitic species on Desmodus rotundus (E. Geoffroy, 1810), that in other areas of cerrado is also parasitised by Trichobius furmani Wenzel, 1966 and Strebla wiedemanni Kolenati, 1856 (Eriksson et al in 2011, Aguiar andAntonini 2011); the absence of Trichobius uniformis Curran, 1935 andStrebla curvata Wenzel, 1976 on Glossophaga soricina (Pallas, 1766), found on this species in cerrado areas (Eriksson et al 2011, in addition to the parasitism by Paraeuctenodes longipes Pessoa et Guimaraes, 1937 recorded in the southern Brazil (Graciolli and Rui 2001). It is also highlighted the absence of parasitism on A. cinereus, a species with register of parasitism by ectoparasitic flies of the genus Neotrichobius Wenzel and Aitken, 1966 in the Amazon region (Guerrero 1994a).…”
Section: Discussionsupporting
confidence: 58%
“…Among the parasitized species found, there was a higher proportion of phyllostomines (46.7%) and nectarivorous (20%) bats than in other studies in the Neotropics with similar capture effort, in which represented less than 40% of species infested (Bertola et al 2005, Eriksson et al 2011, Komeno and Linhares 1999. The species of these groups have more durable shelters, mainly inhabiting hollow trees, caves and nests of termites (Fenton et al 2001, Bernard andFenton 2003).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Comments: This bat fly presents widespread distribution including almost all Brazilian biomes (GRACIOLLI; DIAS et al, 2009;ERIKSSON et al, 2011). Despite being a common species on the lists of bat flies in the Atlantic Forest (AZEVEDO; BERTOLA et al, 2005;SOARES et al, 2013), it was not previously reported in the study by Almeida et al (2011) in the state of Rio de Janeiro, mainly due to not catching S. lilium, which is its primary host (WENZEL, 1976).…”
Section: Resultsmentioning
confidence: 99%
“…Eriksson et al, 2011). Two species are most frequently observed and present a higher prevalence with C. perspicillata: T. joblingi and S. guajiro (Komeno andLinhares, 1999, Rui and.…”
Section: Introductionmentioning
confidence: 99%